Menopausal symptoms are associated with non-adherence to highly active antiretroviral therapy in human immunodeficiency virus-infected middle-aged women - Cutimanco-Pacheco, V. (2020)
Objective: This study aimed to evaluate the association between the intensity of menopausal symptoms and highly active antiretroviral therapy (HAART) adherence in middle-aged women with human immunodeficiency virus (HIV) infection. Methods: In this cross-sectional study, 313 Peruvian women with HIV infection (age 40-59 years) were surveyed and classified as adherent or non-adherent to HAART based on the Antiretroviral Treatment Adherence Evaluation Questionnaire. The intensity of menopausal symptoms was assessed with the Menopause Rating Scale, and categorized as none, mild, moderate, and/or severe. Age, sexual orientation, used HAART scheme, time since HIV diagnosis, menopausal status, risk of depression, and presence of comorbidities were also assessed. Poisson generalized linear models with robust variance were performed in order to estimate crude prevalence ratios (PRs) and adjusted PRs using statistical (a1PR) and epidemiological criteria (a2PR). Results: A total of 19.9%, 32.6%, and 15.0% of all women presented mild, moderate, and severe menopausal symptoms, respectively. Overall, 70.6% women were non-adherent to HAART. The probability of non-adherence was higher in women with mild, moderate, and severe symptoms as compared to asymptomatic women in the non-adjusted model (PR: 1.79, 95% confidence interval [CI]: 1.39–2.29; PR: 1.76, 95% CI: 1.38–2.23; and PR: 2.07, 95% CI: 1.64–2.61, respectively) and the adjusted model. Conclusion: The severity of menopausal symptoms was associated with HAART non-adherence in HIV-infected middle-aged women.